2021
DOI: 10.1172/jci.insight.151911
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 enzymes represent a shared pathogenic pathway in psoriasis and pityriasis rubra pilaris

Abstract: Altered epidermal differentiation along with increased keratinocyte proliferation, is a characteristic feature of psoriasis and pityriasis rubra pilaris (PRP). However, despite this large degree of overlapping clinical and histologic features, the molecular signatures these skin disorders share are unknown. Using global transcriptomic profiling we demonstrate that plaque psoriasis and PRP skin lesions have high overlap, with all differentially expressed genes in PRP relative to normal skin having complete over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 48 publications
0
31
2
Order By: Relevance
“…A recent study by Shao et al using a cPLA 2 inhibitor has suggested that cPLA 2 ε, which is upregulated in keratinocytes by IL‐17A and TNFα, may play an exacerbatory role in psoriasis by producing AA‐derived eicosanoids 28 . However, our present findings argue against this, and in fact indicate that cPLA 2 ε plays a protective role against psoriasis by producing NAEs.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…A recent study by Shao et al using a cPLA 2 inhibitor has suggested that cPLA 2 ε, which is upregulated in keratinocytes by IL‐17A and TNFα, may play an exacerbatory role in psoriasis by producing AA‐derived eicosanoids 28 . However, our present findings argue against this, and in fact indicate that cPLA 2 ε plays a protective role against psoriasis by producing NAEs.…”
Section: Discussioncontrasting
confidence: 68%
“…A recent study by Shao et al using a cPLA 2 inhibitor has suggested that cPLA 2 ε, which is upregulated in keratinocytes by IL-17A and TNFα, may play an exacerbatory role in psoriasis by producing AA-derived eicosanoids. 28 However, our present findings argue against this, and in fact indicate that cPLA 2 ε plays a protective role against psoriasis by producing NAEs. We speculate that the suppressive effect of the cPLA 2 inhibitor on psoriatic inflammation in the study by Shao et al may have resulted from inhibition of cPLA 2 α or some other cPLA 2 isoforms.…”
Section: Gapdhcontrasting
confidence: 61%
See 1 more Smart Citation
“…6B ), suggesting a role in skin barrier function. PLA2G4E is a phospholipase with a proinflammatory function and its expression has been shown to be absent in normal skin, but increased in the upper epidermal layers in patients with psoriasis and pityriasis rubra pillaris ( 53 ). Antibody-based profiling of PLA2G4E ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Increased levels of phospholipase A2 as well as arachidonic acid and its metabolites are found in psoriatic plaques. These factors may increase epidermal cell proliferation and inflammation [ 39 , 40 ].…”
Section: Selection Of Fatty Acidsmentioning
confidence: 99%